Eficacia desinfectante del acido peracetico sobre mesas y en locales de laboratorio. II. Accion micocida - Gonzalez, M.=700 1 Barrera, M.
(Es, En)
Ilus., 16 ref.
Keywords: HIGIENE; DESINFECCION; CANDIDA ALBICANS; ASPERGILLUS NIGER; PENICILLIUM DIGITATUM; HONGOS; LABORATORIOS; CUBA; ACIDO PARACETICO